Time and Cosmology in Plato and the Platonic Tradition - Vázquez, Daniel; Ross, Alberto (Brill's Plato Studies Series, 2022)
The way Plato discusses time and its relation to the cosmos has puzzled and divided his readers from the very beginning. This originated rich and diverse readings that shaped and contributed to the cosmological discussion of the Hellenistic and Late Antiquity periods. Modern scholars too, have offered many and often opposed views on the matter. This book assembles an international team of scholars to move forward the study of Plato's conception of time, to find fresh insights for interpreting his cosmology, and to reimagine the ancient Platonic tradition.